Literature Study of Sukuk as a Sharia Securities Instrument - Sokawati Karina, Rizki; Sri Pujiningsih; Makaryanawati (Economics and Business Journal (ECBIS), 2023)
Sukuk is one of the subjects in the field of Sharia accounting that is growing rapidly in Islamic finance as an alternative investment instrument that has attracted investors' interest in the last few decades. This article aims to provide a deeper understanding of the topics raised, and the theories and methodologies used in research conducted in all countries in the world in the last 10 years (2010-2020). A review of articles from Publish or Perish that is indexed by Scopus and guided by the NVivo R1 application is used to analyze the data. From the results of the study, it was found, firstly about the trend of research on sukuk over the last 10 years by categorizing it from the publishing journal, year of publication, country, and research theme. Second, it was found that there were 29 theories used in previous articles related to the review of the Sukuk literature as an investment in Islamic securities. Furthermore, this theory influences the methods used for research, there are 29 methodologies found in previous articles. Third, the findings regarding research gaps are based on themes for further research